Dynamic Fault Tolerance in Desktop Grids Based On Reliability - Arora, Geeta; Rani, Dr. Shaveta; Singh, Dr. Paramjit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Fault tolerance is an important issue to guarantee reliable execution of tasks in computational desktop grid environment where execution failures are frequently expected, requires the availability of efficient fault tolerant strategies able to effectively deal with resource failures and/or unplanned periods of unavailability. In this paper we present a Dynamic Fault Tolerant strategy that, rather than just tolerating faults as done by traditional fault-tolerant schedulers, exploit the information concerning size of task, resource speed and resource reliability by maintaining resource history to improve application performance. The performance of this strategy has been compared via simulation with those attained by traditional fault-tolerant strategy. Our results, obtained by considering a set of realistic scenarios modeled after real Desktop Grids, show that our approach results in better application performance and resource utilization.